Kontruksi Etika Digital Perspektif Pendidikan Islam Melawan Tantangan Era Society 5.0 - Fatimah Nurfadilah; Dini Pebriana (Hikmah : Jurnal Studi Pendidikan Agama Islam, 2026)
This study aims to map the principles of ethics and adab in the use of digital media from an Islamic perspective, examine their relevance to the dynamics of digital media usage in the contemporary era, and formulate pedagogical implications for the development of digital ethics education in Islamic educational institutions. The ongoing digital transformation, which has altered learning patterns and social interactions, has also given rise to various challenges, including the spread of misinformation, hate speech, and cyberbullying, thereby highlighting the need for a digital ethics framework grounded in Islamic values. The findings reveal five fundamental principles of adab in digital media usage, namely tabayyun as a mechanism for information verification, amanah as the foundation of honesty, qoulan sadidan as a guideline for truthful communication, satr al-awrah as a principle of privacy protection, and muraqabah as an awareness of Allah’s supervision. This study also highlights the phenomenon of FOMO (fear of missing out), which may foster dependence on digital media and shift the spiritual orientation of Muslim adolescents. Therefore, families and educational institutions are encouraged to integrate Islamic values into digital literacy through exemplary conduct, strengthening parental roles, and implementing character-oriented learning in a holistic manner.